Side branch FFR after provisional stenting: simplified approach based on OCT frame count. (25th November 2020) - Kini, A; Okamoto, N; Barman, N; Vengrenyuk, Y; Yasumura, K; Bhatheja, S; Kapur, V; Hasan, C; Sweeny, J; Baber, U; Mehran, R; Stone, G; et al.
Abstract: Background/Introduction: Treatment of bifurcation coronary artery lesions remains a major challenge in interventional cardiology. Side branch (SB) stenoses are frequently observed after stent implantation in bifurcation lesions, although angiographically narrowed SBs may not be functionally significant. Fractional flow reserve (FFR), a pressure-derived index of the hemodynamic significance of a coronary artery stenosis, may be useful in determining whether additional intervention is required in jailed SBs. Angiography and intravascular ultrasound (IVUS) derived parameters have showed poor diagnostic accuracy in predicting the functional significance of jailed SBs. Purpose: The aim of the present study was to use high resolution optical coherence tomography (OCT) imaging to predict functionally significant SB stenoses after provisional stenting defined as SB FFR ≤0.80. Methods: Seventy-one patients with 71 calcified bifurcation lesions with angiographically intermediate SB stenoses undergoing provisional stenting were enrolled in the prospective study. OCT pullbacks were performed before and after stent placement, and SB FFR was measured after main vessel stenting. SB ostium area (SBOA) was assessed using three-dimensional OCT cut-plane analysis off-line. In addition, we developed a simplified approach to SB ostium assessment based on SB ostium frame count using two-dimensional OCT pullback not requiring off-line 3D reconstruction. For the analysis, consecutive frames were counted between the most distal and most proximal take-off of the SB frames. Results: Similar to previous studies, quantitative coronary angiography findings were not associated with the functional significance of SBs after main vessel stenting. In contrast, SBOA assessed by 3D-OCT after provisional stenting strongly correlated with post-procedure SB FFR. The optimal cut-off value for the SBOA area to predict a SB FFR ≤0.80 was 0.76 mm 2 (sensitivity 82%, specificity 89% and area under the curve of 0.92 (95% CI: 0.84–0.99). A simplified approach to SB ostium assessment using OCT frame count yielded a sensitivity of 82%, specificity 89% and area under the curve 0.92 (95% CI: 0.84 to 0.99) with a cut-off of 4.5 frames allowing detection of functionally significant SB stenoses during the procedure in real time. Figure 1 shows a receiver-operating characteristic curve for SB FFR ≤0.8 and a representative case with SB FFR = 0.66 after provisional stenting and SB ostium frame count equal 3 (Frame 1 to 3) Conclusion(s): Assessment of SB using either 3D OCT off-line reconstruction or a simplified approach based on OCT frame count can detect SB branches with FFR ≤0.80 with high sensitivity and specificity. The developed approaches may represent a useful tool to assess provisional stent outcomes. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Boston Scientific; St. Jude Medical